Improving Village Poultry's Survival Rate through Community-based Poultry Health Management: Evidence from Benin - Epiphane Sodjinou; Arne Henningsen; Olorounto D. Koudande (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
Community-based poultry health management (CBM) is a strategy for village poultry improvement based on the installment of "poultry interest groups" in experimental villages. These groups serve as a channel for the dissemination of village poultry improvement technologies. The use of CBM is due to the fact that village poultry farming is practiced in a total or partial scavenging system which gives the impression that all the birds in the village belong to the same flock. Accordingly, actions that target all farmers of the same village may have a larger impact on the village poultry's survival rate than actions that target individual producers. The objective of this study is to assess the impact of CBM on the survival rate of village poultry. Based on data collected on 353 poultry keepers, the study shows that CBM significantly improves the survival rate of village poultry. The adoption of technologies – poultry vaccination, construction of henhouses, and improved feed – disseminated through the CBM also significantly improves the survival rate. The access to markets for inputs and veterinary services is also important in improving the survival rate of poultry. Finally, the study suggests that governments and development agencies can improve village poultry survival rates by investing in the dissemination of information regarding best husbandry management practices through approaches that rely on the community such as CBM because CBM groups serve as channels for the dissemination of village poultry improvement technologies.
Keywords: O13; Q12; Q16; 330; Benin; Community-based management; Survival rate; Two-limit Tobit; Village poultry